Fibreglass Reinforced Composites - Weronika Machowicz-Musiał (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The use of fibreglass products in conservation and available products that can be employed as joints are presented. The experiment relied on comparative tests of load capacity of the dowel joints in wood and fibreglass. The results of this pilot study did not allow to state the advantage of tested fibreglass joints over wood however it opened up the field for further research.